Regionalization of intestinal microbiota and metabolites in the small intestine of the Bactrian camel - Cheng, Yujiao; Ren, Yan; Zhang, Wangdong; Lu, Jia; Xie, Fei; Fang, Ying-Dong; Fan, Xiping; He, Wanhong; Wang, Wenhui (Frontiers in Immunology, 2024)
IntroductionPeyer's patches (PPs) are crucial antigen-inductive sites of intestinal mucosal immunity. Prior research indicated that, in contrast to other ruminants, PPs in the small intestine of Bactrian camels are found in the duodenum, jejunum, and ileum and display polymorphism. Using this information, we analyzed the microbial and metabolic characteristics in various segments of the Bactrian camel's small intestine to further elucidate how the immune system varies across different regions. MethodsIn this study, the microbiota and metabolite of 36 intestinal mucosal samples, including duodenal (D-PPs), jejunal (J-PPs), and ileal PPs (I-PPs), were profiled for six Bactrian camels using 16S rRNA gene sequencing and liquid chromatography with tandem mass spectrometry (LC-MS/MS). To confirm meaningful associations, we conducted connection analyses on the significantly different objects identified in each group's results. ELISA was used to analyze the levels of IgA, IgG, and IgM in the same tissues. ResultsThe microbiota and metabolite profiles of J-PPs and I-PPs were found to be similar, whereas those of D-PPs were more distinct. In J-PPs and I-PPs, the dominant bacterial genera included Clostridium, Turicibacter, and Shigella. In contrast, D-PPs had a significant increase in the abundance of Prevotella, Fibrobacter, and Succinobacter. Regarding the metabolomics, D-PPs exhibited high levels of polypeptides, acetylcholine, and histamine. On the other hand, J-PPs and I-PPs were characterized by an enrichment of free amino acids, such as L-arginine, L-glutamic acid, and L-serine. These metabolic differences mainly involve amino acid production and metabolic processes. Furthermore, the distribution of intestinal immunoglobulins highlighted the specificity of D-PPs. Our results indicated that proinflammatory microbes and metabolites were significantly enriched in D-PPs. In contrast, J-PPs and I-PPs contained substances that more effectively enhance immune responses, as evidenced by the differential distribution of IgA, IgG, and IgM.DiscussionThe intestinal microenvironment of Bactrian camels displays distinct regional disparities, which we propose are associated with variations in immunological function throughout different segments of the small intestine. This study highlights the specific traits of the intestinal microbiota and metabolites in Bactrian camels, offering a valuable reference for understanding the relationship between regional intestinal immunity and the general health and disease of the host.